PENGGUNAAN SOFTWARE SOSIOMETRI UNTUK EKSPLORASI KEMATANGAN SOSIAL PADA MATA KULIAH ASESMENT NON TES - Rochani Rochani; Rauda Zaimah Dalimunthe; Bangun Yoga Wibowo (Jurnal Penelitian Bimbingan dan Konseling, 2019)
AbstractThe non-test psychological assessment techniques is a course that is non-test psychological measurement, so that in the learning process the lecturer prioritizes practice and simulation methods. For further streamline the lecture process, a learning innovation will be developed, namely by developing manual sociometry instruments to be assisted by sociometry software applications. The purpose of this research is development research with stages of pre-implementation, non-test implementation, analysis, and evaluation of non-test software applications. The instrument used has validity. In addition, the use of sociometry software in lectures on psychological testing of non-test techniques can develop student learning independence. The results showed that students' social maturity in interactions in the social, personal, learning, and career fields was still in the low category. This can be seen from the results of the analysis of filling the instruments given by sem students. VI, there are still many students in isolated choices. Key word: sociometry, social maturity